ANALISIS RESETTING PROTEKSI OVER CURRENT RELAY, GROUND FAULT RELAY DAN RECLOSER PADA PENYULANG ABANG DAN FEEDER AMED SETELAH REKONFIGURASI - A. A. Gde Agung Semarabawa; Tjok. Gede Indra Partha; I Gede Dyana Arjana (Jurnal SPEKTRUM, 2019)
Abang feeder receives electricity supply from transformer II 30 MVA GI Amlapura with a line length of 23 kms and has 67 distribution substations with data losses of 0,574 MW. Reducing losses, increasing reliability and continuity, one way to do this is to reconfigure feeders. The feeder reconfiguration will affect the value of the feeder impedance, so the resetting of the Over Current Relay, Ground Fault Relay and Recloser protection systems is needed. Resetting the protection of Amed OCR feeder obtained t value = 0.1 seconds, OCR recloser Tirtagangga obtained t value = 0.2 seconds, and Oang feeder Abang obtained t value = 0.3 seconds. Resetting the protection of the Amed GFR feeder obtained a value of 0.1 seconds, GFR recloser Tirtagangga 0.2 seconds, and GFR feeder Abang 0.3 seconds. The simulation results using the ETAP program are known to coordinate OCR, GFR and recloser already working well with grading time values ? 0.3 second, so it will not cause overlap or trip simultaneously.